Effects of Altering Supplementation Frequency During the Pre-Partum Period of Beef Cows Grazing Dormant Native Range - C. J. McMullen; J. R. Jaeger; J. W. Waggoner; K. R. Harmoney; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2016)
Spring-calving beef cattle that are grazing low-quality (<7% crude protein) dormant forage typically are unable to meet their maintenance requirements for protein. Providing a protein supplement (>30% crude protein) is recommended to decrease losses of body weight and body condition. Nutrient supplementation when forage quality is poor or limited is one of the largest expenditures for forage-based beef cattle operations. The expansion of the ethanol industry has afforded many producers in corn and sorghum-producing regions an alternative to traditional oilseed-based protein supplements. The availability and nutrient profile of distiller’s grains with solubles (DDG) has made it popular as a supplement for cows that are grazing dormant lowquality forages. Decreasing supplementation frequency reduces costs for labor and fuel. Previous research has shown no difference in body weights or body condition scores of cows supplemented with distiller’s grains daily, once every three days, or once every six days; however, the proportion of cows that ate hay during the 60 minutes immediately after supplementation was less on the day of supplementation for cows supplemented once every six days compared to cows supplemented daily. The observed decrease in hay consumption following supplementation could potentially decrease total organic matter intake during late gestation. More frequent supplementation may increase organic matter intake and improve performance during the month before parturition. Therefore, the objective of this study was to evaluate effects of altering frequency of supplementing distiller’s grains during the last 28 days of gestation with respect to performance of spring-calving beef cows consuming low-quality dormant native range.
Keywords: supplementation; gestation; distiller’s grains